2005
DOI: 10.1123/apaq.22.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Coordination Disorder, Self-Efficacy Toward Physical Activity, and Play: Does Gender Matter?

Abstract: This study investigated the effect of gender on the relationship between Developmental Coordination Disorder (DCD) and self-reported participation in organized and recreational free-play activities. A participation-activity questionnaire and the short form Bruininks-Oseretsky Test of Motor Proficiency was administered to a large sample of children ages 9 to 14 (N = 590). A total of 44 children (19 boys, 25 girls) were identified as having probable DCD. Regardless of gender, children with DCD had lower self-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 42 publications
7
65
0
7
Order By: Relevance
“…Na Holanda, um estudo que avaliou 749 crianças, evidenciou 7,7% delas com dificuldade motora (JONGMANS; SMITS-ENGELSMAN; SHOEMAKER, 2003). Já em pesquisa realizada no Canadá, com 564 crianças, apurou-se um percentual de 7,5% de dificuldade significativa de movimento (CAIRNEY et al, 2005).…”
Section: Discussionunclassified
“…Na Holanda, um estudo que avaliou 749 crianças, evidenciou 7,7% delas com dificuldade motora (JONGMANS; SMITS-ENGELSMAN; SHOEMAKER, 2003). Já em pesquisa realizada no Canadá, com 564 crianças, apurou-se um percentual de 7,5% de dificuldade significativa de movimento (CAIRNEY et al, 2005).…”
Section: Discussionunclassified
“…DCD is equally common among boys and girls [2,3], although some epidemiological studies have indicated a male to female prevalence ratio of 2:1 [4]. the etiology of DCD is multi-faceted and complex.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies in children younger than 13 years, it was found that one of the characteristics in children with poor motor skills is usually low levels of physical activity, which supports these results (Cairney et al 2005;Cloete et al 2006;Prinsloo & Pienaar, 2003). Harvey and Mcgill (2007) investigated the correlation between poor motor skills and physical activity in 80 three-year-old and 118 four-year-old children.…”
Section: Introductionmentioning
confidence: 56%
“…Children with poor motor proficiency skills are more inclined to avoid physical activity because they do not possess the skills for the given activity. In this regard, Cairney, Hay, Faught, Mandigo, and Flouris (2005) refer to the long-term consequences of motor deficiencies, namely that physical inactivity goes hand-in-hand with the risk of developing chronic health problems with age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation